Global Governance Perspektif Liberalisme - Robi Cahyadi Kurniawan (PUBLICA, 2011)
The globalization world has brought the changes toward the world condition of politic, social and economy. Although the globalization politic has been more dominating, but its development has become multi dimensional and multi perspective. The raise of global governance is seen as the legitimating need toward the existing world norms. The terminology for the legitimating is the product from the politic that gives the justification. Global Governance is the matter of arrangement in running and executing global politic rules. Global Governance in the view of liberalist is not merely only the norms of independency without any intervention, but also includes the politic activity and sub national, national and supra national level. It also covers the public policy and administration.